Perception of Pregnant Women in Dealing with Pregnancy and Childbirth during COVID-9 Pandemic in Manado - Thesa Soe; John J. E. Wantania; Hermie M. M. Tendean (e-CliniC, 2022)
Abstract: Currently, COVID-19 pandemics has caused many deaths worldwide, therefore, the attitude of pregnant women in dealing with pregnancy and childbirth during this pandemic might be influenced. This study aimed to obtain the perception of pregnant woman in dealing with pregnancy and childbrith during the pandemic in Manado. This was a descriptive and observational survey study with a cross sectional design. Respondents were pregnant women of 1st to 3rd semester that visited two primary health cares: Puskesmas Bahu and Puskesmas Sario Kotabaru Manado.The results showed that most pregnant women were 21-30 years old (65.71%), high school education (68.57), housewife (75.71%), multigravida parity (68.57%), on the third semester (48,57%), and had no history of confirmed Covid-19 (94.29%). Moreover, most of the respondents felt happy when they knew about their pregnancy (68.57%), did routine antenatal care/ANC (71.43%), chose that vaccination was absolutely necessary (45.71%), and had to give birth at a health facility (71.43%). In conclusion, most pregnant women did plan and felt happy of their pregnancies. The majority of respondents chose that vaccination during pregnancy was absolutely necessary, and they would carry out routine antenatal care as usual, and had to give birth at a health facility.Keywords: pregnancy; childbirth; pandemic of COVID-19; perceptionÂ Abstrak: Saat ini pandemi COVID-19 telah banyak menyebabkan kematian di seluruh belahan dunia sehingga dianggap dapat berpengaruh terhadap sikap ibu hamil dalam menghadapi kehamilan dan persalinan di masa pandemi. Penelitian ini bertujuan untuk mengkaji persepsi ibu hamil dalam menghadapi kehamilan dan persalinan pada masa pandemi di Manado. Jenis penelitian ialah observasional deskriptif survei dengan desain potong lintang. Responden ialah wanita hamil mulai dari trimester 1 sampai dengan trimester 3 yang berkunjung ke Puskesmas Bahu dan Puskesmas Sario Kotabaru Manado. Hasil penelitian mendapatkan bahwa karakteristik ibu hamil terbanyak berusia 21-30 tahun (65,71%) dengan pendidikan terakhir SMA (68,57%), pekerjaan IRT (75,71%), paritas multigravida (68,57%), usia kehamilan pada trimseter 3 (48,57%), dan tidak pernah terkonfirmasi Covid-19 (94,29%). Selain itu ibu hamil yang merencanakan kehamilan (71,43%), perasaan senang saat mengetahui sedang hamil (68,57%), melakukan antenatal care/ANC seperti biasa (71,43%), dan merasa harus melakukan persalinan di fasilitas kesehatan (71,43%). Simpulan penelitian ini ialah sebagian besar ibu hamil memang merencanakan dan merasa senang karena kehamilannya. Mayoritas ibu hamil merasa bahwa vaksinasi saat kehamilan mutlak dibutuhkan, melakukan antenatal care seperti biasa, dan harus melakukan persalinan di fasilitas kesehatan.Kata kunci: kehamilan; persalinan; pandemi COVID-19; persepsi